2014
DOI: 10.1371/journal.pone.0096862
|View full text |Cite
|
Sign up to set email alerts
|

Long Bone Structure and Strength Depend on BMP2 from Osteoblasts and Osteocytes, but Not Vascular Endothelial Cells

Abstract: The importance of bone morphogenetic protein 2 (BMP2) in the skeleton is well known. BMP2 is expressed in a variety of tissues during development, growth and healing. In this study we sought to better identify the role of tissue-specific BMP2 during post-natal growth and to determine if BMP2 knockout affects the ability of terminally differentiated cells to create high quality bone material. We targeted BMP2 knockout to two differentiated cell types known to express BMP2 during growth and healing, early-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…Experimental groups were comprised of either all male, all female, or male and female mice as reported in the result tables. The choice of sex was based simply on availability; we did not observe any sex-genotype interactions in this study’s results or our previous phenotyping studies [24]. The conditional knockout (cKO) mice carried two floxed Bmp2 alleles and were Cre-positive ( Bmp2 fl/fl ; Cre-positive).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Experimental groups were comprised of either all male, all female, or male and female mice as reported in the result tables. The choice of sex was based simply on availability; we did not observe any sex-genotype interactions in this study’s results or our previous phenotyping studies [24]. The conditional knockout (cKO) mice carried two floxed Bmp2 alleles and were Cre-positive ( Bmp2 fl/fl ; Cre-positive).…”
Section: Methodsmentioning
confidence: 87%
“…Lastly, after non-damaging mechanical loading that stimulates lamellar bone formation, BMP2 expression is up-regulated [9]. Taken together with findings that BMP2 is critical for post-natal bone formation [20] and that deletion of BMP2 in osteoblast lineage cells results in osteopenia and reduced bone strength [24,25], this result suggests that BMP2 may be critical in loading-induced bone formation.…”
Section: Introductionmentioning
confidence: 95%
“…47 There are a few studies of the correlation between biomechanical parameters and Raman spectroscopic composition parameters in mouse models of disorders, including osteogenesis imperfect (OI) [48][49][50][51] and osteoporosis, 52 as well as on the effects of knocking out matrix proteinase, 53 transcription factor 54 and noncollagenous proteins. [55][56][57][58][59][60][61][62] These are discussed in the following sections.…”
Section: Animal Age Effectsmentioning
confidence: 99%
“…The depletion of osteoblast-derived bone morphogenic protein-2 (BMP2) could cause structural and mechanical defects in long bones of Osx-Cre knockout mice, but Raman spectroscopic analyses could not explain these defects. 60 The authors suggested that other parameters related to collagen alignment, cross-links and structure should be examined. In another study, Raman spectroscopy found that calvarial osteoblastic cell cultures treated with BMP2 in the presence or absence of lysyl oxidase resulted in mineralized tissue with distinct collagen secondary structures 61 Moreover,BMP2 and lysyl oxidase treatment yielded in vitro mineralized tissue with increased hardness and elastic modulus, which were comparable to that of 4-week-old calvarial bone.…”
Section: Fbn2mentioning
confidence: 99%
“…[4][5][6] Few studies, however, have addressed potential angiocrine functions of Bmp2 in vivo. [7][8][9] Recently, 2 nonredundant signaling pathways have been proposed that control hepatic hepcidin expression and iron homeostasis. 10 One pathway comprises Bmp6 signaling via type I (Bmpr1a/Alk3) and type II (Bmpr2) receptors and Smad phosyphorylation in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%